The Soldier Image and State-Building in Modern China, 1924-1945 - Xu, Yan (History teacher) (Book collections on Project MUSE., 2019)
"The Soldier Image and State-Building in Modern China, 1924-1945 is the first study in English to explore the ways in which the figure of the soldier was employed to advance the ideological and cultural agendas of a variety of citizen groups during the first half of the twentieth century in China. Government authorities, cadets at the Whampoa Military Academy (the "West Point of China"), elites, urban professionals, intellectuals, activists, writers and students resisted, collaborated with, or questioned the heroic ideal of the soldier promoted by the Nationalist government. Author Yan Xu casts a wide net, examining military training records, political propaganda, field reports, newspapers, magazines, government documents, memoirs, and novels. In novels and articles, women and teachers worked against the heroic ideal without openly challenging the military, emphasizing the soldier's suffering, emotional needs, and poor education and thereby promoting their own importance as caretakers and educators. Students and young people urged enlistment and idealized the warrior-hero, but also managed to effectively criticize the government by organizing soldier relief work to combat government corruption. Xu demonstrates how the CCP's strategy of building bonds between soldiers and peasants and humanizing heroes was ultimately a more successful political strategy than the GMD's approach of elevating soldiers as model citizens"--